2020
DOI: 10.3390/diagnostics10030152
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Extracellular DNA in Acute Kidney Injury

Abstract: Current diagnostic methods of acute kidney injury (AKI) have limited sensitivity and specificity. Tissue injury has been linked to an increase in the concentrations of extracellular DNA (ecDNA) in plasma. A rapid turnover of ecDNA in the circulation makes it a potential marker with high sensitivity. This study aimed to analyze the concentration of ecDNA in plasma in animal models of AKI. Three different fractions of ecDNA were measured—total ecDNA was assessed fluorometrically, while nuclear ecDNA (ncDNA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…In the murine model of LPSinduced kidney injury, the mtDNA-CN of whole cell lysates declined [73], while the mtDNA-CN of cytoplasmic extracts increased [15], probably indicating that under cell stress, mtDNA replication was restricted but preexisting mtDNA continued to be released from the mitochondria to the cytosol. Analysis of circulating mtDNA-CN revealed that the concentration of mtDNA in plasma tended to increase although not significantly in bilateral ureteral obstruction (BUO) and ischemia-reperfusion models in mice [16]. Compared with circulating mtDNA-CN, urinary mtDNA-(UmtDNA-) CN has greater potential as an ideal indicator for AKI owing to its accessibility, correlation with renal function, and predictive value for kidney prognosis [74][75][76].…”
Section: Mtdna and Kidney Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the murine model of LPSinduced kidney injury, the mtDNA-CN of whole cell lysates declined [73], while the mtDNA-CN of cytoplasmic extracts increased [15], probably indicating that under cell stress, mtDNA replication was restricted but preexisting mtDNA continued to be released from the mitochondria to the cytosol. Analysis of circulating mtDNA-CN revealed that the concentration of mtDNA in plasma tended to increase although not significantly in bilateral ureteral obstruction (BUO) and ischemia-reperfusion models in mice [16]. Compared with circulating mtDNA-CN, urinary mtDNA-(UmtDNA-) CN has greater potential as an ideal indicator for AKI owing to its accessibility, correlation with renal function, and predictive value for kidney prognosis [74][75][76].…”
Section: Mtdna and Kidney Diseasesmentioning
confidence: 99%
“…In agreement, a recent cohort study involving 4812 CKD patients demonstrated that decreased mtDNA-CN in whole blood correlated with increased all-cause mortality and infection-related deaths [ 86 ]. The level of mtDNA-CN in blood cells is negatively correlated with the occurrence and prognosis of CKD, whereas cell-free circulating mtDNA-CN tends to be positively correlated to kidney injury [ 16 ]. Of note, cell-free circulating mtDNA was also detected in abundance in healthy individuals [ 87 ].…”
Section: Mtdna and Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Homolová et al [ 107 ] studied the amount of extracellular DNA (ecDNA) in plasma in animal models of acute kidney injury (AKI). The authors identified three subtypes of ecDNA: mtDNA, nuclear ecDNA (ncDNA), and total ecDNA.…”
Section: Cfdna In Kidney Diseasesmentioning
confidence: 99%
“…We have previously shown that plasma ecDNA is increased in AKI models of glycerol-induced nephropathy and bilateral ureteral obstruction (48 h period), and bilateral nephrectomy (24 h period) [ 17 ]. However, 24 and 48 h are quite long intervals, during which kidney damage might lead to the deterioration of its function.…”
Section: Introductionmentioning
confidence: 99%